The Creeping Concept of Trauma - Haslam, Nick; McGrath, Melanie J (Social research, 2020)
Over the past century, the concept of trauma has substantially broadened its meanings in academic and public discourse. We document four directions in which this semantic expansion has occurred at different times: from somatic to psychic, extraordinary to ordinary, direct to indirect, and individual to collective. We analyze these expansions as instances of "concept creep," the progressive inflation of harm-related concepts, and present evidence for the rising cultural salience and semantic enlargement of trauma in recent decades. Expansive concepts of trauma may have mixed blessings for personal and collective identity.